La nueva ley del informante y su repercusión en el ámbito penal - García-Panasco Morales, Guillermo (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2024)
The purpose of this piece of work is to look into the impact that the entry into force of Law 2/2023, of February 20 or «Informer Law», may have on certain areas of criminal law and criminal procedures. Particularly, the impact of the new information system on the configuration of the criminal liability of legal entities and, singularly, on the content and effectiveness of compliance programs will be addressed. Next, various practical problems will be looked upon, such as the content of internal investigations and the possible impact of some fundamental rights (through the registration of electronic devices or the use of security recordings), with special attention to the guarantees derived from the necessary protection of the rights to defense and to the presumption of innocence of natural and legal persons, so that the proceedings carried out can be used in a penal procedure.